2017
DOI: 10.1039/c7ja00306d
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional characterization of gold nanorods by combining millisecond and microsecond temporal resolution single particle ICP-MS measurements

Abstract: By combining normal and high temporal resolution spICP-MS measurements, the accurate dimensional analysis of nanorods is possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 27 publications
2
27
0
3
Order By: Relevance
“…It can theorized from this result that only an outer shell of the gold core is evaporated, ionized and thus analyzed or that just of an external portion of the ionic cloud is measured by the detector. It has to be pointed out that this 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 12 result is coherent with a recent study demonstrating that SPICPMS is sensitive to nanoparticle shape 30 .…”
Section: Calibrationsupporting
confidence: 88%
See 2 more Smart Citations
“…It can theorized from this result that only an outer shell of the gold core is evaporated, ionized and thus analyzed or that just of an external portion of the ionic cloud is measured by the detector. It has to be pointed out that this 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 12 result is coherent with a recent study demonstrating that SPICPMS is sensitive to nanoparticle shape 30 .…”
Section: Calibrationsupporting
confidence: 88%
“…On the other hand, Single Particle ICPMS (SPICPMS) is still under developments and requires involved process clarification and accuracy improvement. The strategy of this study is the comparison of the two techniques to study comprehensively SPICPMS performance and observe phenomena otherwise hidden.6 spherical gold nanoparticle suspensions distributed over a large size range (30, 50, 60, 80,100 and150 nm) are studied as standards. Potential matrix effect are eliminated by stabilizing nanoparticles with chitosan in HCL.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Through the evaluation of the signal histograms, the technique can provide information about the presence, size distribution, number concentration, elemental or isotopic composition of nanoparticles [21][22][23][24]. In our previous studies, we demonstrated that not only single component or homogenous (random) alloy spherical NPs can be analyzed, and additional information, such as the structure and aspect ratio, can also be obtained by the spICP-MS method [25,26]. The spICP-MS analysis is fast (takes only a couple of minutes) and the required sample volume is small (a few mL).…”
Section: Numerousmentioning
confidence: 99%
“…This information can then be combined with particle diameter or volume data from other NP characterization techniques, such as electron microscopy or dynamic light scattering, towards the calculation of the total pore (void) were optimized prior to the measurements. Plasma sampling depth was optimized using the signal-to-noise ratio as objective function [25]. Dwell time (called integration time in the Agilent nomenclature) was decreased for 28 Si in order to lower the contribution of background to the measured signal.…”
Section: Numerousmentioning
confidence: 99%